Mu-desynchronization, N400 and corticospinal excitability during observation of natural and anatomically unnatural finger movements - Syrov, Nikolay; Bredikhin, Dimitri; Yakovlev, Lev; Miroshnikov, Andrei; Kaplan, Alexander (Frontiers in Human Neuroscience, 2022)
The action observation networks (or the mirror neuron system) are the neural underpinnings of visuomotor integration and play an important role in motor control. Besides, one of the main functions of the human mirror neuron system is recognition of observed actions and the prediction of its outcome through the comparison with the internal mental motor representation. Previous studies focused on the human mirror neurons (MNs) activation during object-oriented movements observation, therefore intransitive movements observation effects on MNs activity remains relatively little-studied. Moreover, the dependence of MNs activation on the biomechanical characteristics of observed movement and their biological plausibility remained highly underexplored. In this study we proposed that naturalness of observed intransitive movement can modulate the MNs activity. Event-related desynchronization of sensorimotor EEG rhythms, N400 ERPs component and corticospinal excitability were investigated in twenty healthy volunteers during observation of simple nontransitive finger flexion that might be either biomechanically natural or unnatural when finger wriggled out towards the dorsal side of palm. We showed that both natural and unnatural movements caused mu/beta-desynchronization, which gradually increased during the flexion phase and returned to baseline while observation of extension. Desynchronization of the mu-rhythm was significantly higher during observation of the natural movements. At the same time, beta-rhythm was not found to be sensitive to the action naturalness. Also, observation of unnatural movements caused an increased amplitude of the N400 component registered in the centro-parietal regions. We suggest that the sensitivity of N400 to intransitive action observation with no explicit semantic context might imply the broader role of N400 sources within action observation networks. Surprisingly, no changes in corticospinal excitability were found. This lack of excitability modulation by action observation could be related with dependence of the M1 activity on the observed movement phase.